2020
DOI: 10.1111/1468-2427.12843
|View full text |Cite
|
Sign up to set email alerts
|

The State as Both Regulator and Player: The Politics of Transfer of Development Rights in China

Abstract: The conventional argument that the introduction of transfer of development rights (TDR) shifts the power of land use regulation from the state to the market is increasingly under challenge. In China, the state's grip on land is reinforced through TDR, in which the state is both regulator and player. This state-dominated form of TDR affects China in three ways. First, competing aspirations of different scales of government complicate how TDR is implemented. Although the central state promotes TDR to maintain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…However, in the process of rapid industrialization and urbanization, the preservation of arable land is increasingly regarded as a heavy political and financial burden by local governments. The problem of substandard compensation land for occupied arable land is widespread, which affects the quality of China's arable land to a certain extent (Zhong et al, 2017;Yang et al, 2018;Shao et al, 2020). Thus, on arable land with relatively worse quality, peasants will adopt intensive farming methods and invest more fertilizers, farm materials, and cultivating labor to increase agricultural output per unit area, which objectively exacerbates agricultural carbon emissions and is not conducive to the improvement of agricultural carbon performance.…”
Section: The Object Of Taxation: Governmentsmentioning
confidence: 99%
“…However, in the process of rapid industrialization and urbanization, the preservation of arable land is increasingly regarded as a heavy political and financial burden by local governments. The problem of substandard compensation land for occupied arable land is widespread, which affects the quality of China's arable land to a certain extent (Zhong et al, 2017;Yang et al, 2018;Shao et al, 2020). Thus, on arable land with relatively worse quality, peasants will adopt intensive farming methods and invest more fertilizers, farm materials, and cultivating labor to increase agricultural output per unit area, which objectively exacerbates agricultural carbon emissions and is not conducive to the improvement of agricultural carbon performance.…”
Section: The Object Of Taxation: Governmentsmentioning
confidence: 99%
“…By establishing the urban land market and housing market [25], the logic of market takes root in the urbanisation within various accumulation regimes at subnational scales (e.g., provincial, municipal, county level). Chinese cities are witnessing an avalanche of complicated state space reorganisation when states themselves involve the emerging market as players and regulators [25,28].…”
Section: Understanding State Restructuring In Chinamentioning
confidence: 99%
“…Scholars often use predictive models to simulate land use, with the goal of improving policy effectiveness [15]. Many studies have found that realizing the carbon peak policy will impact land use changes [16][17][18][19]; however, the link between the policy and those changes have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity and uncertainty of land use, prediction models can help improve the accuracy of policy simulations [15]. Key land use research methods include cellular automata models, CLUE-S and regression analysis, and the CLUMondo land use type simulation model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation